Selective Targeting of Myoblast Fusogenic Signaling and Differentiation-Arrest Antagonizes Rhabdomyosarcoma Cells - Granados, Valerie A. (Cancer Res, 2019)
Rhabdomyosarcoma (RMS) is an aggressive soft tissue malignancy comprised histologically of skeletal muscle-lineage precursors that fail to exit the cell-cycle and fuse into differentiated syncytial muscle - the underlying pathogenetic mechanisms for which remain unclear. In contrast to myogenic transcription factor signaling, the molecular machinery that orchestrates the discrete process of myoblast fusion in mammals is poorly understood, and unexplored in RMS. The fusogenic machinery in Drosophila, however, is understood in much greater detail, where myoblasts are divided into two distinct pools: Founder Cells (FCs) and fusion competent myoblasts (fcms). Fusion is heterotypic and only occurs between FC and fcms. Here, we interrogated a comprehensive RNA-seq database and found that human RMS diffusely demonstrates an FC-lineage gene signature, revealing that RMS is a disease of FC-lineage rhabdomyoblasts. We next exploited our Drosophila RMS-related model to isolate druggable FC-specific fusogenic elements underlying RMS, which uncovered the Epidermal Growth Factor Receptor (EGFR) pathway. Using RMS cells, we showed that EGFR inhibitors successfully antagonized RMS RD cells, while other cell lines were resistant. EGFR inhibitor-sensitive cells exhibit decreased activation of the EGFR intracellular effector Akt, while Akt activity remained unchanged in inhibitor-resistant cells. We then demonstrate that Akt inhibition antagonizes RMS – including RMS resistant to EGFR inhibition – and sustained activity of the Akt1 isoform preferentially blocks rhabdomyoblast differentiation potential in cell culture and in vivo. These findings point towards selective targeting of fusion- and differentiation-arrest via Akt as a broad RMS therapeutic vulnerability.